2011
DOI: 10.2106/jbjs.j.00160
|View full text |Cite
|
Sign up to set email alerts
|

Hounsfield Units for Assessing Bone Mineral Density and Strength: A Tool for Osteoporosis Management

Abstract: Hounsfield units obtained from clinical computed tomography scans that are made for other purposes correlate with dual x-ray absorptiometry scores as well as compressive strengths based on osseous models and potentially provide an alternative method for determining regional bone mineral density at no additional cost to the patient. The information could conceivably be applied toward fracture risk assessment, diagnosis of osteoporosis, and early initiation of needed treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

22
627
4
17

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 652 publications
(670 citation statements)
references
References 15 publications
22
627
4
17
Order By: Relevance
“…First, we used CTderived HU to estimate the degree of BMD reduction. Although the gold standard for measuring BMD is the DEXA scan, several studies demonstrate the utility of diagnostic CT scan in providing reliable estimates for regional bone strength and BMD [10][11][12][13]. Secondly, this study is a retrospective review of patients treated at a single institution.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…First, we used CTderived HU to estimate the degree of BMD reduction. Although the gold standard for measuring BMD is the DEXA scan, several studies demonstrate the utility of diagnostic CT scan in providing reliable estimates for regional bone strength and BMD [10][11][12][13]. Secondly, this study is a retrospective review of patients treated at a single institution.…”
Section: Discussionmentioning
confidence: 99%
“…Although dual-energy X-ray absorptiometry (DEXA) serves as the gold standard for BMD quantification, several studies have determined that the BMD provided by DEXA has a strong correlation with CT-derived Hounsfield units (HU), can provide reliable estimates for regional bone strength and BMD, and accurately rule out osteoporosis with better than 90% sensitivity [10][11][12][13]. Since diagnostic CT scans are ordered routinely to monitor response to treatments, we can utilize CT-derived HU to monitor BMD in patients, while avoiding the need for additional DEXA imaging and improving resource utilization.…”
mentioning
confidence: 99%
“…In dentistry CT is still used to evaluate the alveolar bone before implant placement, and the HU values are considered to give the objective and reliable information on the amount and quality of bone [6,7] compared to the subjective in its nature classification system of Lekholm and Zarb [8,9] The increasing application of CBCT to bone density assessment impelled researchers to evaluate the new system in relation to CT. Some studies showed that bone density measurements of the same selected regions in jaws made by means of both methods were not corresponding to each other [10,11] displaying higher HU values for CBCT images [8,10].…”
mentioning
confidence: 99%
“…This measure has been shown to be an accurate and reproducible estimate of bone mineral density, and compares favourably to either dual x-ray absorptiometry or to mechanical testing of subchondral bone strength [15,16,17,22,26].…”
Section: Methodsmentioning
confidence: 96%